Daur ʻIlm al-Lugah al-Ijtimā’ī fī Taʻlīm al-Lugah al-ʻArabiyyah li Gair an-Nāṭiqīn Bihā - Imam Wahyudi (INAIFAS PRESS, 2021)
Sociolinguistics is a science that discusses the use of language in society and how language can be embedded in social relations in society, the social background of a speaker and the meaning of what is conveyed, and issues that touch the character and social identity of a speaker. The existence of a social environment is one aspect that determines success in teaching foreign languages. The purpose of this article was to specifically explain the role of sociolinguistics in teaching Arabic to non-native speakers. Researcher used descriptive qualitative approach by reviewing indepth sociolinguistic theories in playing a role in learning Arabic to non-native speakers. The results of the research showed that sociolinguistic theories had strong correlation in teaching Arabic for non-native speakers. Sociolinguistics can be used as a guide in preparing learning tools and solving practical problems in teaching Arabic.